Salting Stories: 鹽憶家餚 - Lim, Daenia Ching (Nanyang Technological University, 2022)
Salting Stories was created with the preservation of family recipes in mind, focusing on creating deeper engagement, interaction and understanding of one’s heritage and identity through storytelling. Food often captures the essence of life’s collective experiences, building memories upon our palette via sensorial stimulations and a deep longing for emotional connections. While family recipes are often lost over time, Salting Stories adopts a visual approach to preserve and disseminate the history and heritage of these valuable family assets, for generations to come. It is an intimate view into the stories and meanings behind my family’s recipes – providing personal insights into my identity.